2021
DOI: 10.1016/j.amsu.2021.102594
|View full text |Cite
|
Sign up to set email alerts
|

Global burden of acute myocardial injury associated with COVID-19: A systematic review, meta-analysis, and meta-regression

Abstract: Background The body of evidence showed that there is a strong correlation between acute myocardial Injury and COVID-19 infection. However, the link between acute myocardial infection and COVID-19, the prevalence, reliability of diagnostic modalities, independent predictors, and clinical outcomes are still uncertain and a topic of debate. The current study was designed to determine the prevalence, determinants, and outcomes of acute myocardial injury based on a systematic review and meta-analysis t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 91 publications
0
22
0
1
Order By: Relevance
“…Myocardial injury appears to be linked to severity of COVID-19 disease and mortality [ 4 10 ]. Mortality from COVID-19 is reported to be higher among hospitalized patients with myocardial injury, compared to those without, [ 4 , 6 , 7 , 11 , 12 ]. Indicating that myocardial injury may portend a poorer prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Myocardial injury appears to be linked to severity of COVID-19 disease and mortality [ 4 10 ]. Mortality from COVID-19 is reported to be higher among hospitalized patients with myocardial injury, compared to those without, [ 4 , 6 , 7 , 11 , 12 ]. Indicating that myocardial injury may portend a poorer prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…HF is among the most frequently reported cardiovascular complications related to COVID-19 infection, being diagnosed in up to 24% of patients, while venous thromboembolism was identified in 21% of cases, followed by dysrhythmias and myocarditis in 17% and 7% of patients, respectively [ 5 , 6 , 27 , 28 ]. The main risk factors for SARS-CoV-2-induced acute cardiac injury include smoking, male gender, and comorbidities, including diabetes mellitus, arterial hypertension, and coronary artery disease [ 10 , 11 ]. The imbalance between pro-inflammatory and anti-inflammatory mediators may be responsible for the development of major cardiovascular events [ 29 ].…”
Section: Cardiovascular Pathophysiology Related To Covid-19 and The M...mentioning
confidence: 99%
“…A plethora of studies show that approximately one in every three patients with COVID-19 will develop a certain phenotype of myocardial injury [ 7 , 12 , 13 ], the risk being significantly higher in patients with previously diagnosed chronic coronary heart disease [ 14 ]. Additional supporting evidence concerning acute cardiac injury due to coronavirus infection was provided by a large meta-analysis performed by Abate et al which reported an alarming 22.3% prevalence of myocardial injury in patients who tested positive for SARS-CoV-2 [ 10 ].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, experts predict that the global burden of cardiovascular disease will grow exponentially over the next few years because of the increased prevalence of diabetes and due to the long-term effects of the current COVID-19 pandemic ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%